2009
DOI: 10.1002/jms.1622
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase behavior of radical cations of perfluoroalkyl‐1,2,4‐triazines: an experimental and theoretical study

Abstract: Electron ionization mass spectrometry and low-energy collision-induced decomposition reactions occurring in a tridimensional ion trap, together with density functional theory (DFT) calculations on neutrals, even- and odd-electron cations, have been used to study the gas-phase ion chemistry of a series of perfluoroalkyl-1,2,4-triazines. Loss of oxygen, due to thermal degradation occurring before ionization, likely involving the hydroxylamino group, has been observed. Compounds having a carbonyl group at positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As a part of an ongoing synthetic research program toward the synthesis of s ‐triazine derivatives for structural investigation and evaluation of their biological activity, we have synthesized a new series of 2,4,6‐tri substituted s ‐triazines . The applications of electron ionization and electrospray ionization (ESI) mass spectrometry to various substituted triazines are well known in the literature . Tandem mass spectrometric experiments have shown that the dissociation of protonated molecules containing more than one benzyl groups yield product ion of m/z 181 having molecular formula C 14 H 13 + due to benzyl‐benzyl interactions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a part of an ongoing synthetic research program toward the synthesis of s ‐triazine derivatives for structural investigation and evaluation of their biological activity, we have synthesized a new series of 2,4,6‐tri substituted s ‐triazines . The applications of electron ionization and electrospray ionization (ESI) mass spectrometry to various substituted triazines are well known in the literature . Tandem mass spectrometric experiments have shown that the dissociation of protonated molecules containing more than one benzyl groups yield product ion of m/z 181 having molecular formula C 14 H 13 + due to benzyl‐benzyl interactions .…”
Section: Introductionmentioning
confidence: 99%
“…[16] The applications of electron ionization and electrospray ionization (ESI) mass spectrometry to various substituted triazines are well known in the literature. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Tandem mass spectrometric experiments have shown that the dissociation of protonated molecules containing more than one benzyl groups yield product ion of m/z 181 having molecular formula C 14 H 13 + due to benzyl-benzyl interactions. [37][38][39][40][41][42] Examples include study of the protonated dibenzyl esters of dicarboxylic acid generated by chemical ionization [40] and N,N 0 -dibenzylpiperzines produced by ESI.…”
Section: Introductionmentioning
confidence: 99%